2015
DOI: 10.1111/psyg.12108
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dementia severity and behavioural and psychological symptoms in early‐onset Alzheimer's disease

Abstract: Background: The features of behavioural and psychological symptoms of dementia (BPSD) are influenced by dementia stage. In early-onset Alzheimer's disease (EOAD), the association between BPSD and dementia stage remains unclear because of the difficulty of recruiting subjects with a wide range of disease severity. We used a combination of community-based and hospital-based approaches to investigate the relationship between dementia severity and BPSD in EOAD patients. Methods: Sixty-three consecutive EOAD outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 34 publications
5
51
1
6
Order By: Relevance
“…This study suggests that significant differences exist in caregiver burden and BPSD between two types of dementia and that BPSD contribute to caregiver burden. The behavioral changes noted in FTD patients in this study were similar to those observed in previous reports (Diehl, Forstl, Jansen, & Kurz, 2004;Tanaka et al, 2015). [8,9] In this study we found that the caregivers of FTD patients had higher burden scores than caregivers of AD patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study suggests that significant differences exist in caregiver burden and BPSD between two types of dementia and that BPSD contribute to caregiver burden. The behavioral changes noted in FTD patients in this study were similar to those observed in previous reports (Diehl, Forstl, Jansen, & Kurz, 2004;Tanaka et al, 2015). [8,9] In this study we found that the caregivers of FTD patients had higher burden scores than caregivers of AD patients.…”
Section: Discussionsupporting
confidence: 91%
“…The behavioral changes noted in FTD patients in this study were similar to those observed in previous reports (Diehl, Forstl, Jansen, & Kurz, 2004;Tanaka et al, 2015). [8,9] In this study we found that the caregivers of FTD patients had higher burden scores than caregivers of AD patients. Riedijk et al, [10] like us, found that the caregivers of patients with FTD experienced a greater burden than those of patients with AD.…”
Section: Discussionsupporting
confidence: 91%
“…The cumulative use of antipsychotics was approximately 37% in the two-year follow-up which means that the number of participants using antipsychotics more than doubled (2.4 times) during our follow-up. Research in young-onset Alzheimer's dementia has shown no positive association of delusions, depression or anxiety with increasing dementia severity (Tanaka et al, 2015). Furthermore, we also found that the two-year dementia progression in the NeedYD cohort was limited to less than one point on the GDS (Gerritsen et al, 2018).…”
Section: Discussionmentioning
confidence: 51%
“…More than 70% of the patients in this study had moderate to severe dementia. Higher severity of dementia is often accompanied by increased behavioural and psychological symptoms, 29 administration of more medications, including BZDRs. 30 Up to 50% of nursing home residents with dementia were reported to be treated with BZDRs for BPSD.…”
Section: Discussionmentioning
confidence: 99%